HPV genotyping in cervical cancer in Northern Thailand. Adapting the linear array HPV assay for use on paraffin-embedded tissue - Siriaunkgul S. (2014)
Objectives.: The aims of this study were to determine the prevalence of HPV infection and distribution of HPV genotypes in Northern Thai women and thereby estimate the benefit of administering the HPV vaccine in the population. Methods.: Formaldehyde-fixed, paraffin-embedded samples of invasive squamous cell carcinoma from 99 patients were tested for HPV genotypes using the Linear Array HPV Genotyping Test. Results.: HPV was detected in 96/99 (96.9%) cases. Seventy-five (78.1%) cases were single infections and 21 (21.9%) multiple. HPV16 and HPV18 were the most common subtypes, detected in 62/96 (64.4%) cases. HPV52 and HPV58 infections were found in 17/96 (17.7%) cases. Co-infection always involved HPV16. The most common co-infection was HPV16 and 52 (7 cases) but never HPV16 and 18. Conclusions.: Although the prevalence of HPV infection in cervical cancer of Northern Thai women is comparable to the other regions worldwide, the distribution of HPV subtypes differs with lower frequencies of HPV16 and 18, and higher frequencies of HPV52 and 58. Moreover, multiple infections are common. The vaccine against HPV16 and HPV18 can be estimated to prevent approximately two thirds of the cervical cancer cases in Northern Thailand. Although designed for use on unfixed tissue, this study shows that the Linear Array HPV Genotyping Test can be successfully used for HPV genotyping on paraffin-embedded archival tissue. This methodology also provides a means for retrospective studies on serial samples for a greater understanding of HPV genotypes, co-infections, and relationship to cervical cancer. © 2007 Elsevier Inc. All rights reserved.